Flavonoid content of Phaleria macrocarpa fruit and its proximate compositions - Abd Gani, Siti Salwa; Noor Ezzuddin, Najat Nabilah; Zaidan, Uswatun Hasanah; Halmi, Mohd Izuan Effendi; Abd Halim, Alyaa Nurathirah (Malaysian Society of Applied Biology, 2023)
Flavonoids are one of the compounds in phenolic compounds in fruits. Flavonoids have been documented to modulate or modify lipid peroxidation, free radical scavenging activity, and inhibition of hydrolytic and oxidative enzymes. Flavonoids also influence anti-inflammatory action, anti-tumour, anti-hyperglycemia, anti-viral, anti-microbial, and anti-fungal effects. In this research, flavonoid content in P. macrocarpa fruits was determined, as well as its proximate compositions. To extract flavonoids in the fruit, P. macrocarpa fruits were extracted by the Soxhlet extraction method using aqueous as a solvent. Total flavonoid content in P. macrocarpa fruit extract was 89.89 ± 3.71 mg QE/100 mL. Proximate analyses were conducted to determine the fruit’s moisture content, ash content, dry matter, crude protein, crude fibre, and crude essential oil. Results obtained for proximate composition were 9.45 ± 2.67% (crude protein), 21.633 ± 1.17 (fibre), and 5.605 ± 0.88 (essential oil). Moisture content in this fruit was 88.401 ± 0.749%, the dry matter was 10.96%, and the ash content was 6.33 ± 3.72%. FTIR analysis shows the extract’s functional spectra of phenol, alkane, alkene, and alkyne groups.